The complex ritual dynamics of individual and group experience in the temple, as imagined in the Mishnah - Cohn, Naftali S. (2019)
When the mishnaic authors narrated the Temple rituals of the past, they made choices in how to imagine the nuanced dynamics of actors, spaces, objects, and actions that make up the ritual enactments. These choices point to their understanding of how Temple ritual worked and what it accomplished. Taking an unusual feature of many of the Mishnah's Temple-ritual narratives—the shifting back and forth between singular and plural, or, between individual and group—as a starting point, this article argues that for the rabbis of the Mishnah, Temple ritual bound together every Israelite with the collective whole, while simultaneously allowing for individuality. Moreover, it created a sense of solidarity and belonging within multiple levels of Jewish collective life—the whole people, the local city or town, and the lineal groupings of Israelite, Levite, and priest. Similarities to mishnaic rules about prayer-centered rituals, moreover, suggest that the rabbis believed these functions of ritual continued even in the absence of the Temple.